2012
DOI: 10.1007/s10488-012-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

The Session Report Form (SRF): Are Clinicians Addressing Concerns Reported by Youth and Caregivers?

Abstract: This study explores the relationship between clinician-reported content addressed in sessions, measured with the Session Report Form (SRF), and multi-informant problem alerts stemming from a larger battery of treatment process and progress measures. Multilevel multinomial logit models were conducted with 133 clinicians and 299 youths receiving home-based treatment (n = 3,143 sessions). Results indicate a strong relationship between session content and problems related to youth symptoms and functioning as repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A follow-up study on the relationship between clinician-reported content addressed in sessions and concurrent multi-informant problem alerts found several differences in session content based on type of problem alert and reporter. Clinicians reported addressing content related to emotional, family, and friend/peer problems more when reported by youths, while content related to youth behavioral problems occurred more when reported by caregivers (Douglas Kelley et al, 2012). High-risk problems (alcohol/substance use, harm to self or others) were strongly correlated with session content when reported by anyone (clinician, youth, or caregiver).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A follow-up study on the relationship between clinician-reported content addressed in sessions and concurrent multi-informant problem alerts found several differences in session content based on type of problem alert and reporter. Clinicians reported addressing content related to emotional, family, and friend/peer problems more when reported by youths, while content related to youth behavioral problems occurred more when reported by caregivers (Douglas Kelley et al, 2012). High-risk problems (alcohol/substance use, harm to self or others) were strongly correlated with session content when reported by anyone (clinician, youth, or caregiver).…”
Section: Discussionmentioning
confidence: 99%
“…They are the same sub-sample used in the previous study (Douglas Kelley et al, 2012) that explored the relationship between clinician-reported session content and concurrent multi-informant problem alerts. All clients had presenting problems encompassing a range of common youth mental health issues (e.g., mood and anxiety disorders, school problems, oppositional behavior, and impulsivity/attention deficit disorders) and were receiving ‘treatment as usual’ mental health care, typically in home-based settings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SRF is completed every session during treatment and discharge. See Kelley, Vides de Andrade, Sheffer, & Bickman (2010) and Kelley, Vides de Andrade, Bickman, and Robin (2012; this issue) for more information on the SRF.…”
Section: Measures Included In the Ptpb (2nd Ed)mentioning
confidence: 99%